The Human Genome Project - Levy, Janey (History just before you were born., 2019)
Explores the origins, history, and outcomes of the Human Genome Project, which began in the 1990s and ended in the early 2000s when the project fully sequenced, allowing scientists and doctors to know the full extent of the human genetic code. Discusses what this means for medicine and disease treatment and how it might help researchers in the future eliminate gene-based diseases. Includes a glossary.